55 Stem cell reduces intimal thickening in experimental porcine vein grafts. Issue 20 (23rd September 2011) - Huang, W C; Sala-Newby, G B; Lewis, A; Stratford, P W; Newby, A C; Murphy, G J
Abstract : Rational for the Study: Long term patency of autologous saphenous vein coronary bypass grafts is limited by neointima formation and atherosclerosis. Neointima is promoted by adventitial hypoxia. Hence we investigated the effect on neointima in pig vein-into-artery interposition grafts of peri-adventitial application of immortalised human mesenchymal stem cells that express the angiogenic peptide, Glucagon Like Peptide-1. Cells were protected from immune mediated destruction by encapsulation in alginate microbeads. Methodology: Cellbeads (20 000cell/cm 2 ) were applied onto adventitia in Ringer's solution during grafting and were compared to alginate beads without stem cells or vehicle treated grafts. Results: CellBeads significantly reduced neointima area after 4 weeks compared to alginate beads (mean difference 4.1 mm 2, 95% CI 0.3 to 7.9, p=0.033) or vehicle (mean difference 4.0 mm 2, 95% CI 0.3 to 7.7, p=0.030). CellBeads provoked a significant increase in vein graft adventitial neoangiogenesis vs alginate beads (mean difference 16.8 vessels/ mm 2 95% CI 3.4 to 30.3, p=0.012) or vehicle (mean difference 18.0 vessels/ mm 2 95% CI 5.1 to 31.0, p=0.006). CellBeads had no effect on vessel inward or outward remodelling and promoted adventitial collagen deposition. CellBeads treated grafts had higher patency (6/7) than alginate beads without stems cells (6/17, Fisher's Exact test p=0.052) and similar to vehicle-treated grafts (7/8 grafts patent), There was no evidence of an inflammatory (macrophage) or immune (lymphocyte) reaction to either CellBeads or alginate beads. Conclusions: Periadventitial human stem cells inhibit early neointima formation and accelerate adventitial angiogenesis in experimental porcine vein grafts. The alginate beads alone exhibited unexpected graft failure which will need to be understood before further translational development.